Presenting Workshops to Adults - Brian E. Myers (EDIS)
AEC-385, a 3-page illustrated fact sheet by Brian E. Myers, provides workshop presenters with key characteristics of correctly designed workshops for adult learners. Includes references. Published by the UF Department of Agricultural Education and Communication, August 2007.